2016
DOI: 10.1371/journal.pone.0160557
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Kidney and Psoas Muscle Proteins as Indicators of Post-Mortem Interval in a Rat Model, with Use of Lateral Flow Technology

Abstract: We investigated potential protein markers of post-mortem interval (PMI) using rat kidney and psoas muscle. Tissue samples were taken at 12 h intervals for up to 96 h after death by suffocation. Expression levels of eight soluble proteins were analyzed by Western blotting. Degradation patterns of selected proteins were clearly divided into three groups: short-term, mid-term, and long-term PMI markers based on the half maximum intensity of intact protein expression. In kidney, glycogen synthase (GS) and glycogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 39 publications
3
19
0
1
Order By: Relevance
“…However, from the low number of human samples in this study, it cannot be concluded whether there is a statistical decrease of the native band in later postmortem stages, as it was the case in rat vastus lateralis muscle. The significant decomposition of GAPDH protein in rats over a PMI of 96 hpm is confirmed by the proteomic analysis and by a study reporting postmortem GAPDH decrease in rat psoas muscle [ 17 ] over a similar period of time. Despite the trend to decrease, the presence of the native band of GAPDH band at a PMI of 96 hpm and the occurring degradation products at a larger PMI in the human sample H3 indicate possible applicability as a marker in later postmortem stages.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…However, from the low number of human samples in this study, it cannot be concluded whether there is a statistical decrease of the native band in later postmortem stages, as it was the case in rat vastus lateralis muscle. The significant decomposition of GAPDH protein in rats over a PMI of 96 hpm is confirmed by the proteomic analysis and by a study reporting postmortem GAPDH decrease in rat psoas muscle [ 17 ] over a similar period of time. Despite the trend to decrease, the presence of the native band of GAPDH band at a PMI of 96 hpm and the occurring degradation products at a larger PMI in the human sample H3 indicate possible applicability as a marker in later postmortem stages.…”
Section: Discussionmentioning
confidence: 60%
“…Postmortem changes, such as the loss of the native protein band or the occurrence of specific degradation products, were additionally shown to significantly correlate with the PMI. Among these proteins are calcineurin A, protein phosphatase 2A [ 13 ], titin, nebulin [ 14 ], desmin, troponin [ 15 ], vinculin [ 16 ], AMP-activated protein kinase, caspase 3, and glycogen synthase [ 17 ]. Furthermore, PMI-dependent desmin and cardiac troponin T degradation has been confirmed in humans [ 15 ] and was already successfully applied to obtain evidence about the succession of events in a criminal case [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…This constitutes a major advantage in both research (e.g., multiple samples can be taken and analyzed, without interference by previous samplings) and practical application (e.g., even in severely injured bodies or body parts, there is a high chance to be able to collect unaffected tissue for analysis). Available data, however, is largely limited to thigh muscle [ 5 8 ], with few exceptions (e.g., M. psoas [ 9 ], M. gastrocnemius [ 10 ]). To fully benefit from the described advantages of muscle tissue, further research is required regarding decomposition similarities and deviations within individual muscles, between muscles, and between muscle types (skeletal muscle, cardiac and smooth muscle).…”
Section: Introductionmentioning
confidence: 99%
“…Saber and Ali (2016) showed a strong positive linear correlation between mRNA levels of Caspase-3 in the gastrocnemius muscle with time passed since death. They found a raise in mRNA levels of caspase-3 began 2 h postmortem until 6 h then a marked reduction occurred at 8 h. Lee et al (2016) has been reported that caspase-3 was completely degraded 84-96 h post-mortem (PMI 50 value = 26.3 h) in kidney by western blot and 76% of the stained area for caspase-3 was reduced gradually 48 h after death and totally absent at 96 h after death by immunohistochemistry. In another study, caspase levels started to decrease after 32 h post-mortem (Kemp et al, 2010).…”
Section: Discussionmentioning
confidence: 97%